Geogames and Geoplay Game-based Approaches to the Analysis of Geo-Information (Advances in Geographic Information Science, 2018)
This book brings together contributions from researchers, GIS professionals and game designers to provide a first overview of this highly interdisciplinary field. Its scope ranges from fundamentals about games and play, geographic information technologies, game design and culture, to current examples and forward looking analysis. Of interest to anyone interested in creating and using Geogames, this volume serves as a channel for sharing early experiences, discussing technological challenges and solutions, and outlines a future research agenda. Games and play are part of human life, and in many game activities, place, space and geography plays a central role in determining the rules and interactions that are characteristic of each game. Recent developments and widespread access to mobile information, communication, and geospatial technologies have spurred a flurry of developments, including many variations of gaming activities that are situated in, or otherwise connected to the real world. .